Student Perceptions of Changes in Teaching Models after the Covid-19 Pandemic in Developing 21st Century Skills (A Study Case in Japanese Language Education Study Program, Universitas Negeri Semarang) - DWI PUSPITOSARI; Dwi Puji Asrini (Universitas Negeri Semarang, 2023)
This study aims to determine the impacts of the Pandemic on the development of 4C skills and learning motivation. 21st-century skills are a collection of skills humans need to face the times. The skills are creative thinking, critical thinking and problem-solving, communication, and collaboration (4C). Students in the 21st century need at least one of these skills to communicate their ideas effectively, think creatively, solve problems, and make wise decisions independently or in groups. The Covid-19 pandemic has had a significant impact on all life sectors, including education. There has been a significant change in the learning model from face-to-face learning to online or hybrid learning. This study uses an online questionnaire distributed to the students of Universitas Negeri Semarang Japanese language education study program. We collected the data from a total of 115 students. The questionnaire results, which were distributed to 115 students, found that the offline learning model was felt to hone the development of 4C skills. Regarding learning motivation, it was found that 76% of respondents felt that learning motivation had decreased, and 24% answered that they did not experience a decrease in learning motivation.